Producing the Research Article: Support and Assistance by the Mentors - Joshi, Rajendra Prasad (Journal of Durgalaxmi, 2022)
Mentoring and Co-Writing for Research Publication Purposes Pascal Patrick Matzler Routledge, 2022, 165 pp. ISBN: 978-1-003-15263-7